Responsive teaching and the beginnings of energy in a third grade classroom - DAVID HAMMER; FRED GOLDBERG; SHARON FARGASON (Metaichmio Publications, 2012)
Energy, like "the whole of science...is nothing more than a refinement of everyday thinking" (Einstein, 1936). It is a refinement in two respects, both conceptually, in the particular canonical features of the concept, and epistemologically, in the kind of intellectual pursuit the concept supports. Drawing on data from the third author's third-grade class, we show evidence of children's productive conceptual and epistemological resources for understanding energy. We discuss how responsive teaching can help students tap into and refine these resources, as well as the notion of responsive curriculum and our first steps in designing a prototype.